Large scale manufacturing of puree-only edible films from onion bulb (Allium cepa L.): Probing production and structure–processing–property correlations - Dias, Diogenes dos Santos [UNESP]; Otoni, Caio Gomide; da Silva, Robson Rosa; Meneguin, Andreia Bagliotti; Mattoso, Luiz Henrique Capparelli; Barud, Hernane da Silva; Ribeiro, Clovis Augusto [UNESP] (Elsevier, 2020)
The demand for bioplastics from renewable sources for a range of emerging applications has been as extensive as the efforts to find greener routes for their isolation from nature. Surfing this wave, we report on the production of flexible, optically semi-transparent onion-only bioplastics through different all-aqueous film-forming procedures encompassing hydrothermal, grinding, washing, and/or sieving pre-solvent casting steps. The onion bioplastics were extensively characterized targeting correlations among chemical structure, film-forming protocol, and film properties. HPLC evidenced insoluble carbohydrates/polysaccharides in all samples, though at different contents (11–44%) depending on processing, but washing lixiviated all soluble carbohydrates – the presence of ca. 14% of the latter in unwashed samples provided their films with reduced glass transition temperature – from 73–83 to 13 °C, as indicated by DSC; elastic modulus and tensile strength – from 1.5–3.2 GPa to 47 MPa and from 7–21 to 3 MPa, respectively; increased elongation at break – from 0.7–1.6% to 22%; and decreased contact angle with water – from 39-70° to 22° (in comparison with washed samples). Additionally, SEM provided morphological aspects; thermogravimetry indicated thermal stability profile; FTIR led to hydrogen bond energy [kJ] and distance [Å] as well as total crystallinity index (0.43–0.96), lateral order index (0.8–3.2), and hydrogen bonding intensity (13–4.7); and XRD determined the index of crystallinity (21–49%). Finally, the hydrophilic/hydrophobic nature, water barrier, and moisture sorption of the bioplastics were determined. Altogether, we herein depict the production of novel bioplastics made up exclusively of onion and used a range of characterization techniques to come up with relevant structure-processing-property correlations.
Keywords: Casting film-forming; Green processing; Hydrothermal treatment; Optically semi-transparent films; Puree-only edible onion films